Ideološki učinki mestne prenove - Križnik, Blaž (Urbani izziv, 2005)
In this paper we want to show some social consequences of transition from an industrial towards post-industrial city, where the transformation of the Poblenou district in Barcelona will be used as a case study. At the beginning we will show how a city can become a vehicle of ideological texts and how production of city space always involves immediate ideological effects. We will see how the integration of Barcelona's economy into global economy and its structural transformation significantly influence transformation of the Poblenou district and thus directly condition everyday experience of the city for its citizens. On the contrary, the Barcelona city council shows economically motivated transformation of the district as urgent renewal of a "problematic neighbourhood", which is supposed to be in the interest of its inhabitants. This is precisely the point, where ideological effects of hegemonistic city representations needs to be rethought - not just as instruments to impose corporate or bureaucratic top-down interests, but also as a medium for normalisation of the individual and homogenisation of the citypopulation. As an example we will show the case of Kolizej in Ljubljana in the conclusion.
Keywords: Barcelona; mesta; prenova; urbani razvoj